BS EN 62271-209 AMD1. High-voltage switchgear and controlgear. Part 209. Cable connections for gas-insulated metal-enclosed switchgear for rated voltages above 52 kV. Fluid-filled and extruded insulation cables. Fluid-filled and dry-type cable-terminations (1st May 2020) - British Standards Institution,
No abstract available